Training to Make Simple Songs with the Theme of Religious Moderation for Middle School Students in Jayapura Regency - Marlissa, Magdalena s; Polhaupessy, Yustinus; Ristua, Yohanna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Community Service activities carried out by lecturers at the STAKPN Sentani Church Music Department focused on training in creating songs with the theme of religious moderation for junior high school students in Jayapura Regency. Considering the importance of instilling the values of tolerance and harmony among the younger generation, this training teaches basic song creation techniques while emphasizing the role of music as a medium for conveying social messages. Through demonstration and question and answer methods, students are actively involved in the creative process, where they learn to combine technical elements of music with relevant moral messages. The results of this training show an increase in students' awareness of the importance of living in harmony amidst religious diversity. The songs created by students function as a peace campaign tool, conveying messages of peace and tolerance that are easy to understand. Thus, this activity not only improves students' musical skills, but also forms characters who are empathetic and open to differences, making them agents of change in a pluralistic society. Through this initiative, it is hoped that a younger generation will be formed that is more critical and plays an active role in promoting harmony in their environment.